The New Law of the Russian Federation on Protection of Competition and Antimonopoly Legislation of the EU - V. A. Gorbachev (Московский журнал международного права, 2008)
Two years ago in Russia became effective the new antimonopoly legislation. The necessity of making radical changes in the competition law was evident as it did not meet the demands and requirements of the growing Russian economy.The new Russian Law on protection of competition replaces two laws that regulated competition on financial and goods markets. It introduces new definitions and concretizes already existing antimonopoly terminology and notions. The amendments that were made are based on the existing local and international court practices and cases and related decisions of the Russian and EU antimonopoly bodies.In particular, the article considers the following problems and issues:1. the newest statutory interpretation of the meaning “goods” and “market place”;2. amended meaning of the term “dominant position” and “abuse of dominant position”;3. amended meaning of the terms “agreements” and “coordination of economic activities”;4. amended and clarified meaning of the terms “monopoly low price” and “monopoly high price”.In the article also considered some related aspects of the EU antimonopoly practice with the respect of possible application of the existing EU experience for the Russian competition regulation and practice.